Nanoscale phase engineering of niobium diselenide - Bischoff, Felix (2019)
With the continuing miniaturization of semiconductor microelectronics, atomically thin materials are emerging as promising candidate materials for future ultrascale electronics. In particular, the layered transition metal dichalcogenides (TMDs) have attracted a significant amount of attention because of the variety of their electronic properties, depending on the type of transition metal and its coordination within the crystal. Here, we use low-temperature scanning tunneling microscopy (STM) for the structural and electronic phase engineering of the group V TMD niobium diselenide (NbSe2). By applying voltage pulses with an STM tip, we can transform the material crystal phase locally from trigonal prismatic (2H) to octahedral (1T), as confirmed by the concomitant emergence of a characteristic (√13 × √13)R13.9° charge density wave (CDW) order. At 77 K, atomic-resolution STM images of the junction with sublattice detail confirm the successful phase engineering of the material, as we resolve the difference in the Nb coordination evidenced by a slip of the top Se plane. Different 1T-CDW intensities suggest interlayer interactions to be present in 1T-NbSe2. Furthermore, a distinct voltage dependence suggests a complex CDW mechanism that does not just rely on a star-of-David reconstruction as in the case of other 1T-TMDs. Additionally, bias pulses cause surface modifications inducing local lattice strain that favors a one-dimensional charge order over the intrinsic 3 × 3 CDW at 4.5 K for 2H-NbSe2, which can be reversibly manipulated by STM.